Simplified Control Strategies for Power Converters in a Grid-Connected Hybrid DC-AC Microgrid - Busarello, Tiago Davi Curi; Simões, Marcelo Godoy; Laaksonen, Hannu; Kauhaniemi, Kimmo (IEEE, 2023)
Many typical converter control strategies used in microgrids are complex or require modifications in the power structure. The complexities are due coupling effects among controllers and time-delay caused in exchanging information in the system. This paper proposes simplified control strategies for power converters in a grid-connected hybrid DC-AC microgrid, aiming to ensure precise voltage and current regulation. The used controllers are proportional-resonant, integral-double-lead, proportional-integral and single integral controller. In this paper, the methodology for tuning each controller is carefully described in detail and recommendation for choosing their bandwidth is given. Then, the designed controllers are discretized through the Backward-Euler approximation. The power converters of the microgrid are an inverter, a Buck, a Boost and a bidirectional DC-DC. A case study is conducted through simulations with Matlab/Simulink. Results show that the controlled variables follow their reference signals with negligible steady-state error, proving the efficacy of the simplified control strategies and allowing an stable operation of the microgrid.
Keywords: Hybrid Microgrid; Power Control; Power Converters; Photovoltaic systems; Battery storage; fi=Sähkötekniikka|en=Electrical Engineering|